Analysis of Iran's rainfall fluctuations in drought and wet conditions (1991-2021) - Maryam َAriaSadr; Dariush Rahimi (مطالعات جغرافیایی مناطق خشک, 2024)
Aim: Extreme rainfall fluctuations are one of Iran's environmental challenges. The heavy rains of 2019 and the relative drought of 2018 and 2021 show the unevenness of rainfall.Material & Method: This study utilized the daily rainfall data from 360 weather stations spanning the years 1990 to 2021, along with the synoptic indices of the winter seasons of 2019 and 2021. The geographical range of the data, spanning from latitude N 10-90 to longitude E º 10-90, was chosen to provide a comprehensive view of the Iranian climate.Finding: The probability of drought is 42%, drought is 35.5%, and normal conditions are 22.5%. Markov chain indicated the highest probability of normal drought to drought at 57% and consecutive drought at 46.2%. ANOVA showed a significant difference between the climatic variables of wet and dry years. Observational conditions showed that in the wet year (2019) sample year, the Siberian high-pressure center operator had more pressure (1054 megabytes) in 2019 and 1032 mb in 2021. In the wet year, the frequency of cyclones and the temperature difference at the level of 500-1000 are higher, but the omega values are lower. These conditions are for the drought (2021), the amount of pressure in Siberia, the temperature difference between 500 and 1000 is less, and Omega is more (stable air).Conclusion: The amount of rainfall in Iran fluctuates from year to year, and low rainfall years occur more often than high rainfall years.Innovation: Planners should increase the risk of water supply and development and plan based on the minimum amount of precipitation. The physical capacity of the country's ecology should be reviewed, and population concentration in limited areas should be avoided to reduce the vulnerability of the country's geographical environment.